2016
DOI: 10.1080/14647273.2016.1214754
|View full text |Cite
|
Sign up to set email alerts
|

Effect of infertility on quality of life of women: a validation study of the Turkish FertiQoL

Abstract: The fertility quality of life (FertiQoL) measure specifically evaluates the impact of fertility problems in various life areas. The aim of this study was to examine the relationship between FertiQoL and the hospital anxiety and depression scale (HADS) in the Turkish population. All female patients who underwent various fertility treatments in our infertility clinic from May 2011 to May 2014 were approached to participate in the study and 389 completed the questionnaires. Our results showed that the four core s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
30
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 28 publications
4
30
0
Order By: Relevance
“…In a Dutch sample, the total FertiQoL scores that corresponded to the clinical cut off for anxiety and depression were 59 and 52, respectively (Aarts et al, 2011). Using similar methodology, cut offs of 55 and 52, respectively, were reported for women in Turkey (Dural et al, 2016) whereas another study of Turkish women found the same cut offs as the Dutch sample (Kahyaoglu Sut & Balkanli Kaplan, 2015). In an Italian study, FertiQoL Relational scores below around 74 corresponded to marital dysfunction on dyadic adjustment questionnaire (range 74 to 84, depending on measure, Donarelli et al, 2016).…”
Section: B) Clinically Important Thresholdsmentioning
confidence: 79%
See 1 more Smart Citation
“…In a Dutch sample, the total FertiQoL scores that corresponded to the clinical cut off for anxiety and depression were 59 and 52, respectively (Aarts et al, 2011). Using similar methodology, cut offs of 55 and 52, respectively, were reported for women in Turkey (Dural et al, 2016) whereas another study of Turkish women found the same cut offs as the Dutch sample (Kahyaoglu Sut & Balkanli Kaplan, 2015). In an Italian study, FertiQoL Relational scores below around 74 corresponded to marital dysfunction on dyadic adjustment questionnaire (range 74 to 84, depending on measure, Donarelli et al, 2016).…”
Section: B) Clinically Important Thresholdsmentioning
confidence: 79%
“…FertiQoL subscales were correlated with cognate measures of psychological and interpersonal functioning. For example, three showed that higher depression and anxiety were related to lower FertiQoL scores (Aarts et al, 2011;Chi et al, 2016;Dural et al, 2016). Some of the associations between psychological vulnerability and FertiQoL were mediated by other variables.…”
Section: Fertility Quality Of Life Tool Review 12mentioning
confidence: 99%
“…Moreover, there is reasonable evidence for adequate linguistic validation of FertiQoL [ 86 ] as confirmed by a plethora of data collected from several populations [ 8 , 89 92 ]. This support that PROs of FertiQoL reliably measures QoL in women facing infertility and prove that infertility significantly reduces female QoL by increasing anxiety and depression levels [ 6 8 , 89 92 ]. Both conditions belong to the emotional domain independently of the infertility cause and constitute stressful stimuli (namely distress) acting on the HPA and SAM frameworks as previously described.…”
Section: Methodsmentioning
confidence: 99%
“…Although the reliability and validity of the distress scale used for considering the concurrent validity have been confirmed, the use of scales such as HADS, which is frequently used globally, was better [24] [25]. For example, the QoL and anxiety and depression scores of the infertility patients were significantly negatively related when using FertiQoL and HADS [26] [27].…”
Section: Validity and Reliability Of The Japanese Version Of Fertiqolmentioning
confidence: 99%